The interrelationship between basic psychological needs, intrinsic motivation, classroom engagement, and L2 academic achievement: A large-scale study of self-determination theory - Alharfi, Ahmed; Alamer, Abdullah (Studies in Second Language Learning and Teaching, 2025)
Applications of self-determination theory in second or foreign language (L2) learning have continuously provided crucial implications but remain limited in terms of sample scope and the comprehensiveness of tested models. This is particularly important in a large yet under-researched context such as Saudi Arabia, as it enables a stronger assessment of the external validity of the theory. In this study, data were collected from 815 undergraduate students across 35 universities in the country to examine the relationships among the three basic psychological needs, intrinsic motivation, classroom engagement, and grade point average (GPA) in English as an L2. Results showed that variable levels were moderate. A series of one-way ANOVAs indicated that all study variables were consistent across age, gender, and geographical location. Using set-exploratory structural equation modeling (set-ESEM), we found that the effect of the three basic psychological needs and intrinsic motivation on GPA was solely indirect through classroom engagement. Moreover, the influence of classroom engagement on GPA was itself indirectly mediated by intrinsic motivation. Implications for both theory and L2 educational practice are discussed.